A prediction model for aroma quality of Vietnamese orthodox black teas by combined multivariate analysis of GC/MS and sensory evaluation data - Tuan, Hoang Quoc; Thinh, Nguyen Duy; Minh Tu, Nguyen Thi (Vietnam Journal of Science and Technology, 2016)
Relationships between sensory aroma and the volatile composition of 04 black tea grades produced from Northern Vietnam were studied. Consumer preference test on the aroma was carried out by 80 consumers to evaluate the aroma quality of these samples. Aroma concentrate was prepared by Brewed Extraction Method (BEM) method and analyzed using GC/MS. Partial Least Squares Regression (PLSR) was used to determine the relationship between preference scores and peak area percentage data of 39 detected volatile compounds. Among these compounds, 20 identified compounds were determined to contribute significantly to the perceived aroma quality of OTD black teas. On the basis of these 20 compounds, the PLSR model was constructed to predict the aroma quality of OTD black teas. The result showed that the volatile composition by GC/MS in the profiling with sensory and multivariate data analysis should be a useful reference for aroma quality prediction of OTD black tea grades.